Peningkatan Enterpreneurship Anak melalui Cooking Class pada Anak Kelompok B Di TK Bandar Madani Parepare - Nurmadinah; Kurniawati; Tadzkirah; Ashari, Novita; Natsir, Tri Ayu Lestari; Kholilah, Ema Ainun; Haryati, Kusma; Rahmah, Umrah Jabal (Early Childhood Islamic Education, 2024)
The purpose of this study is to increase children's knowledge about entrepreneurship education from an early age, of course, through cooking class activities that will be held for group B children at Bandar Madani Parepare Kindergarten. In this study using a qualitative method, namely with a descriptive approach that provides an overview in the form of sentences as data information for researchers in their initial activities of collecting information. The results of research on cooking class activities to increase child entrepreneurship showed that 13 children experienced a significant increase after the children carried out these activities. This is in accordance with the indicators of entrepreneurship, namely independence, creativity, risk taking, leadership, action orientation, and hard work. Keywords: early childhood, entrepreneurship, cooking class